Renal allograft rejection: investigation of alloantigen presentation by cultured human renal epithelial cells. - Kirby, J A (1991)
Defined lines of primary human renal epithelial cells were established and their expression of class II major histocompatibility (MHC) antigens was up-regulated by culture with interferon-gamma (IFN-gamma). The ability of these cells to stimulate the proliferation of allogeneic peripheral blood mononuclear cells (PBMC) was compared with that of endothelial cells and splenic mononuclear cells. It was found that both endothelial and splenic cells stimulated lympho-proliferation but that cultured renal epithelial cells were non-stimulatory. The failure of proliferation by allogeneic lymphocytes in culture with epithelial cells was not overcome by treatment with interleukin-1 (IL-1) or indomethacin. However, addition of IL-2 to mixed cultures of allogeneic PBMC and renal epithelial cells stimulated lympho-proliferation and allowed the generation of lymphoid cell lines which mediated non-specific lysis of renal epithelial cell lines. Stimulation of PBMC by mixed lymphocyte culture yielded an allospecific T-cell line which was added either to renal epithelial cells from the same donor as the stimulator cells used in the priming reaction or from a third-party donor; lympho-proliferation was observed in the specific secondary reaction but not in the non-specific reaction. These findings indicate that class II MHC antigen-expressing epithelial cells within a renal allograft may not initially stimulate the proliferation of resting allospecific recipient lymphocytes. However, within a rejecting graft it is likely that high local concentrations of IL-2 are present and that many of the infiltrating allospecific lymphocytes will be primed by previous contact with donor antigen-presenting cells, such as vascular endothelial cells or dendritic cells. Therefore, expression of class II MHC antigens by epithelial cells within the microenvironment of a renal allograft may render such cells immunogenic and able to play a direct role in the lymphocyte-mediated intragraft rejection process.